A modelling approach on the impact of an oxide layer on the hydrogen permeation through iron membranes in the Devanathan-Stachurski cell. (1st October 2018) - Vecchi, L.; Pecko, D.; Van den Steen, N.; Mamme, M. Haile; Özdirik, B.; Van Laethem, D.; Van Ingelgem, Y.; Deconinck, J.; Terryn, H.
Abstract: The diffusion and trapping of hydrogen in iron alloys is commonly studied using the Devanathan-Stachurski cell. In this cell, the hydrogen flux through a metal membrane is studied. At the exit side of the membrane, an oxide layer is commonly developed and stabilized as a consequence of the anodic polarization imposed. The process of hydrogen diffusion through the oxide layer and its consecutive oxidation is not fully understood yet. In this paper, we propose a modelling approach that provides additional insights in this process. In particular, we highlight the impact that the presence of the oxide layer can have on the overall hydrogen transport throughout the metal membrane. Moreover, we highlight the complexity of this mechanism and discuss the possible reactions taking place in and at this interface. As a conclusion a possible alternative process to explain the findings is proposed.